International Reserve Adequacy in the Gambia - Tereanu, Eugen (Washington, D.C. : International Monetary Fund, 2010)
This paper applies intertemporal models of precautionary saving to compute an optimal level of international reserves for The Gambia. The analysis focuses on current account shocks specific to a low-income economy with a significant import component and complements a more standard, rule-of-thumb reserve adequacy assessment. The results suggest a central range from 4.5 months to 7 months of imports, which is broadly aligned with the recent actual coverage. Notwithstanding parameter sensitivity, the simulations allow for more informed policy decisions that balance flexibility with a prudent approach to reserve use.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet